Molecular mechanism of lipopolysaccharide (LPS) in promoting biomineralization on bacterial surface - Gong, Zechuan; Guo, Junhui; Li, Qichang; Xie, Hao (Biochimica et biophysica acta. General subjects, 2023)
Biomineralization on bacterial surface is affected by biomolecules of bacterial cell surface. Lipopolysaccharide (LPS) is the main and outermost component on the extracellular membrane of Gram-negative bacteria. In the present study, the molecular mechanism of LPS in affecting biomineralization of Ag+/Cl− colloids was investigated by taking advantages of two LPS structural deficient mutants of Escherichia coli. The two mutants were generated by impairing the expression of waaP or wbbH genes with CRISPR/Cas9 technology and it induced deficient polysaccharide chain of O-antigen (ΔwbbH) or phosphate groups of core oligosaccharide (ΔwaaP) in LPS structures. There were significant changes of the cell morphology and surface charge of the two mutants in comparing with that of wild type cells. LPS from ΔwaaP mutant showed increased ΔHITC upon interacting with free Ag+ ions than LPS from wild type cells or ΔwbbH mutant, implying the binding affinity of LPS to Ag+ ions is affected by the phosphate groups in core oligosaccharide. LPS from ΔwbbH mutant showed decreased endotherm (ΔQ) upon interacting with Ag+/Cl− colloids than LPS from wild type or ΔwaaP mutant cells, implying LPS polysaccharide chain structure is critical for stabilizing Ag+/Cl− colloids. Biomineralization of Ag+/Cl− colloids on ΔwbbH mutant cell surface showed distinctive morphology in comparison with that of wild type or ΔwaaP mutant cells, which confirmed the critical role of O-antigen of LPS in biomineralization. The present work provided molecular evidence of the relationship between LPS structure, ions, and ionic colloids in biomineralization on bacterial cell surface. [Display omitted] •Two mutants were generated to induce deficient O-antigen or core oligosaccharide in LPS.•Significant changes of cell morphology and surface charge were observed of the two mutants.•LPS with deficient phosphate groups of core oligosaccharide showed increased ΔHITC upon interacting with free Ag+ ions.•LPS with deficient polysaccharide chain of O-antigen showed decreased exotherm upon interacting with Ag+/Cl− colloids.•Biomineralization of Ag+/Cl− colloids was affected on cell surface with defective O-antigen structure in LPS.